Impacts of fall Armyworm, groundnut rosette, and soybean rust diseases on smallholder welfare and the effectiveness of control strategies - Mulungu, Kelvin H.; Innocent Pangapanga-Phiri; Ngoma, Hambulo (Wiley, 2025)
Smallholder farmers in Malawi and Zambia face significant challenges to their food security and welfare owing to the increasing prevalence of crop pests and diseases, such as the fall armyworm (FAW), groundnut rosette virus (GRV), and soybean rust. As climate change is projected to exacerbate these threats, understanding their impact and identifying effective control strategies is crucial. This study aims to determine the impact of these pests on crop yields, household income, and food security, as well as to evaluate the effectiveness of various control strategies using survey data from 1100 farmers in Malawi and Zambia. The descriptive results show that approximately 70% of the farmers experience FAW attacks in their maize fields, approximately 28% experience rosette in their groundnuts, and 40% of the farmers report soybean rust infestations. The econometric results show that FAW, rosette, and soybean rust result in 13.5%, 27.2%, and 25.2% yield loss in maize, groundnuts, and soybean, respectively. We also find that the FAW negatively affects income and food security. While rust, rosette, and their combination had no significant effect on income and food security, their combination with FAW led to a greater negative impact than the FAW alone. Although farmers employ multiple strategies to control these pests/diseases, we find evidence, albeit not robust to different estimation strategies, that pesticides, crop rotation, and the use of improved seeds aid in reducing the negative effect of pests/diseases on crop yields. These findings contribute to the growing body of evidence that can inform policies and interventions aimed at enhancing food security and supporting resilient farming systems in sub-Saharan Africa.